Analisis Kuat Tekan Beton dengan Pemanfaatan Silica Fume dan Fly Ash Sebagai Pengganti Semen Sebagian - Rahmadona, Efrilia; Amalia, Kiki Rizky; Ulfah, Luthfiyah; Praditya, Norca (Jurnal Talenta Sipil, 2024)
Construction activities require concrete as a widely used material. Concrete consists of several compositions, namely fine aggregate, coarse aggregate, water, and Portland cement as the main material for the binder. Cement production contributes around 6% of carbon emissions which can damage the environment, including global warming, and the use of high levels of cement material in concrete mixtures, so alternative materials are needed to replace cement or cement additives for concrete mixes. Alternative materials used in this research are fly ash and silica fume. This research aims to determine the test results and characteristics of concrete using silica fume and fly ash as partial cement substitute materials as well as the effect of the ratio of silica fume and fly ash on the compressive strength of concrete. The research was carried out by direct testing in the laboratory. The various mixtures of Fly Ash (FA) and Silica Fume used are: FA 10% and SF 5%, FA 15% and SF 5%, FA 20% and SF 20%, FA 25% and SF 10%. Based on the results of compressive strength tests carried out at 28 days of concrete, it shows that the use of silica fume and fly ash to replace cement cannot be said to have succeeded in increasing the strength of the concrete. The highest compressive strength value was achieved by variation 3, namely with a fly ash content of 20% and 10% silica fume, producing a compressive strength value of 19.44 Mpa, this shows that the strength achieved is still limited to low quality concrete below 20 Mpa.